Scaling up ART in Rwanda: the financial and economic costs - Karengera, Stephen (Health Economics Unit, 2023)
Rwanda has been rolling-out free antiretroviral treatment (ART) since 2004. This scale up could only be realised through significantly increased funding to the HIV/AIDS sub-account. Funding grew from US$9 million in 2003 to US$43 million in 2004 (UNAIDS, 2006b) and has continued to grow since this time given increased grants from GFATM and PEPFAR. Although international funding has been pivotal in the initiation of ART roll-out in resource poor settings, national programmes must look inwards for long term sustainability. This raises the question of whether the country will be able to sustain this level of funding once these grants cease ot are significantly reduced. This question could be answered to a large extent if one knew the lifetime costs of providing ART in Rwanda and the capacity of the country to raise domestic revenue. Unfortunately the body of evidence on unit and lifetime costs for providing ART in Rwanda is nonexistent. The study aimed to determine the economic costs of scaling up ART in Rwanda. Costing from the provider's perspective was undertaken based on data from 3,310 patients in 3 ART sites. The health care utilisation and cost data obtained, supplemented by appropriate secondary data, were used to estimate the cost perpatient period and lifetime costs. These were then used to model the costs of scaling up and to explore the financial sustainability of ART in Rwanda.